Thoracic evaluation and cardiac measurement using radiography in opossums (Didelphis albiventris) - Eduarda Aléxia Nunes Louzada Dias Cavalcanti; Guilherme Albuquerque de Oliveira Cavalcanti; Raqueli Teresinha França (Semina: Ciências Agrárias, 2022)
Cardiac measurement by chest X-ray is very important in the cardiac characterization of dogs and cats, however, the wild animal clinic has a different reality. Opossums (Didelphis albiventris) are part of the Brazilian fauna and are frequently referred for clinical and radiographic evaluation. The objective of this research was to evaluate the thorax of skunks and establish the average of VHS and VLAS for these animals. Chest radiographs were performed in lateral and ventrodorsal projections to measure the VHS and VLAS, thoracic depth and tracheal diameter. The mean VHS was 7.85 (± 0.3) for males and 8.12 (± 0.5) for females and the measured VLAS was 1.19 (± 0.2) for both sexes. The mean value for thoracic depth was 1.13 (± 0.03) and the ratio between the diameter of the chest inlet and the diameter of the trachea was 0.25 (± 0.02), with no significant differences between the sexes. This is the first study that addresses the thoracic evaluation by tracheal and cardiac measurements of skunks through radiographic examination.